Identification of Cleaved Haptoglobin in the Serum of Bee Venom-Hypersensitive Patients - Jae-Min Ryu; Han-Heom Na; Jin-Sung Park; Byung-Soo Ahn; Keun-Cheol Kim (Medical Association of Pharmacopuncture Institute, 2021)
Background : Bee venom has been used as a therapeutic compound for various human diseases in oriental medicine; however, it can induce anaphylaxis in hypersensitive patients during treatment. Anaphylaxis is an acute allergic reaction that occurs after allergen exposure. IgE is released from immune-related cells such as mast cells and basophils during anaphylaxis. Various inflammatory mediators are also released into the bloodstream during the acute response. Objectives: We aimed to identify specific proteins from bee venom-hypersensitive patients. Methods : We analyzed the blood serum of control and bee venom-hypersensitive patients using two-dimensional (2D) electrophoresis. Results : An interesting protein spot with a molecular size of 10 kDa was identified at an isoelectric point (p.I.) of 5.5. Spots detected both before and after sweet bee venom therapy were not proteins induced by sweet bee venom. The 10 kDa protein was identified as the cleaved form of haptoglobin through liquid chromatography-tandem mass spectrometry (LC-MS/MS) analysis. Statistical analysis indicated that the presence of the spot was highly significant in the bee venom-hypersensitive group. Conclusion : The findings suggest that cleaved haptoglobin may be a significant diagnostic protein for anaphylaxis. In addition, a high incidence of bee venom hypersensitivity may be associated with the haptoglobin genotype.